2008
DOI: 10.1121/1.2816569
|View full text |Cite
|
Sign up to set email alerts
|

Across-channel interference in intensity discrimination: The role of practice and listening strategy

Abstract: Pure tone intensity discrimination thresholds can be elevated by the introduction of remote maskers with roved level. This effect is on the order of 10 dB [10log(ΔI/I)] in some conditions and can be demonstrated under conditions of little or no energetic masking. The current study examined the effect of practice and observer strategy on this phenomenon. Experiment 1 included observers who had no formal experience with intensity discrimination and provided training over six hours on a single masked intensity di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Furthermore since the performance of some listeners (e.g., L1 and L4) had not plateaued by the end of the study, further learning may have been possible. This release from across-channel interference is consistent with Buss (2008), who found that six of eight listeners improved with practice on an analogous intensitydiscrimination in unpredictable-noise task. However, widespread learning is contrary to Neff and Dethlefs (1995), where tone-in-unpredictable-noise DLs appeared 'remark-ably stable' in most listeners.…”
Section: Learningsupporting
confidence: 88%
“…Furthermore since the performance of some listeners (e.g., L1 and L4) had not plateaued by the end of the study, further learning may have been possible. This release from across-channel interference is consistent with Buss (2008), who found that six of eight listeners improved with practice on an analogous intensitydiscrimination in unpredictable-noise task. However, widespread learning is contrary to Neff and Dethlefs (1995), where tone-in-unpredictable-noise DLs appeared 'remark-ably stable' in most listeners.…”
Section: Learningsupporting
confidence: 88%
“…Buss (2008) reported that listeners (nZ8) improved during six training sessions (approx. 5500-9000 total trials) on intensity discrimination with a 50 dB sound pressure level (SPL) target tone of 948.7 Hz presented simultaneously with tonal maskers at 0.3 and 3 kHz that were roved in intensity from 42 to 58 dB SPL.…”
Section: (D) Signal Detection and Intensity Discrimination (I) Signalmentioning
confidence: 99%
“…(ii) Intensity discrimination We are aware of only one investigation that provides information on generalization of learning on intensity discrimination, the ability to distinguish small differences in the intensity of a stimulus. Buss (2008) reported that listeners (nZ8) improved during six training sessions (approx. 5500-9000 total trials) on intensity discrimination with a 50 dB sound pressure level (SPL) target tone of 948.7 Hz presented simultaneously with tonal maskers at 0.3 and 3 kHz that were roved in intensity from 42 to 58 dB SPL.…”
Section: (D) Signal Detection and Intensity Discrimination (I) Signal Detectionmentioning
confidence: 99%
“…However, under some conditions, it appears to be difficult or impossible for human listeners to process the outputs of some channels, while ignoring others. This is manifested in effects such as across-channel masking (Schooneveldt and Moore, 1987; Moore et al , 1990), modulation detection interference for amplitude and/or frequency modulated tones (MDI, Yost and Sheft, 1989; Yost and Sheft, 1990; Moore et al , 1991), pitch discrimination interference (PDI, Gockel et al , 2004; 2005), interference with detection of an increment in level of a tone by amplitude modulation of a spectrally distant tone (Gallun and Hafter, 2006), and disruption of intensity discrimination by a spectrally remote sound that is roved in level (Buss, 2008). …”
Section: Introductionmentioning
confidence: 99%